Integrating Sustainable Food Security Policies and the Circular Economy through the Optimisation of Soya - Bajuri, Diding; Widuri, Anye; Awalluddin , Muhammad Aiman; Fitria, Nurul Jannah Lailatul (DAWUH : Islamic Communication Journal, 2026)
Food security is vital to people’s lives as a basic human need. Consequently, the role of the government both central and local is essential in ensuring food security. Policies relating to food security are geared towards achieving food self-sufficiency and food sovereignty. Appropriate policy strategies are required to achieve sustainable food security through improved management of local resources. One strategy that can be implemented is the circular economy model. Sustainable food security through a circular economy system can be realised through the production and consumption of natural resources, for example soya beans. This is an interesting area for research, particularly in Majalengka, which is a leading soybean-producing region and is renowned for its distinctive local processed products. The study employed a descriptive qualitative approach. The results of the study indicate that the integration of sustainable food security policies and the circular economy in the soya bean sector in Majalengka requires synergy between a comprehensive policy framework, the coordinated involvement of subsystems, clear and measurable policy objectives, and effective policy instruments.